Pengaruh Kepuasan Gaji, Pelatihan kerja dan kompentensi terhadap kinerja karyawan: Studi kasus Perusahaan Alih Daya PT Prima Karya Sarana Sejahtera - Astri Melani; Edy Hartono; Evangelia Yuninda (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to determine the effect of Salary Satisfaction, Job Training, and Competence on Employee Performance at PT. Prima Karya Sarana Sejahtera (PKSS). This research employs a quantitative approach using the multiple linear regression analysis method, processed with IBM SPSS Statistics 29. The sample consisted of 100 respondents selected through the purposive sampling technique. Data were collected through a closed-ended questionnaire using a five-point Likert scale, and the research instrument was tested for validity and reliability before use. The results show that the regression model used meets all the classical assumption tests, including normality, multicollinearity, heteroscedasticity, linearity, and autocorrelation. Simultaneously, Salary Satisfaction, Job Training, and Competence have a significant effect on Employee Performance, with a coefficient of determination of 77.4%, while the remaining 22.6% is explained by other factors outside this research model. However, partially, only the Competence variable has a positive and significant effect on Employee Performance, whereas Salary Satisfaction and Job Training do not show significant effects. These findings emphasize that improving employee competence is the key factor in enhancing performance at PT. Prima Karya Sarana Sejahtera. Therefore, the company should focus on developing employee competencies through continuous training programs, professional development, and mentoring systems to improve the overall quality of its human resources.